Typhlocoelum cucumerinum (Rudolphi, 1809): Morpho-pathology of Rare Tracheal Fluke in an Indian Runner Duck - N. Babu Prasath; K. Thilagavathi; J. Selvaraj; J. Hariharan; A. Latchumikanthan; P.C. Prabu; R. Velusamy (The Indian Veterinary Journal, 2024)
Trematodiasis are known to cause economic losses in duck farming. Occurrence of tracheal fluke in ducks are uncommon. Among them, Typhlocoelum cucumerinum was not reported yet from India. Morphology and pathology of a rare tracheal fluke Typhlocoelum cucumerinum was described in an Indian runner ducks. An Indian runner duck flock had a history of mortality in adult birds with clinical signs of nasal and ocular discharge, gasping and torticollis. A dead bird was presented for necropsy. Postmortem examination showed presence of live dorso-ventrally flat, pink flukes in the anterior trachea. Flukes and representative tissue samples were collected and processed as per standard techniques. Lungs showed scattered firm consolidated areas. Upper respiratory passage and nasal sinus mild mucosal congestion covered by viscous contents and necrotic foci respectively. Microscopically, necrotic pneumonia, sub-acute tracheitis and bronchitis, chronic fibrino-purulent sinusitis with parasitic eggs were observed in lungs and upper respiratory air passage respectively. Collected flukes were processed and identified as Typhlocoelum cucumerinum based on the morphology. Lesions in the lungs and upper respiratory passage supported the migration of the flukes from pulmonary vasculature to trachea. Further, presence of eggs in the nasal passage concluded that the pathology observed is due to Typhlocoelum cucumerinum. This paper described the report on pathology and morphology of Typhlocoelum cucumerinum in Indian runner duck.